Providing the Military Forces with Human Resources by Means Of Creation and Development of the Social Institution of Military Instructors as a Element of the Mechanism of Public Administration - Medvid, Mykhailo; Zvieriev, Mykola (Pressing Problems of Public Administration, 2019)
In Ukraine, there are no adequate conditions for social protection of combatants, which contributes to the increase of social tension in society. As a result, new variants of mechanisms of social protection of people with the formed military competencies appear that can function without the participation of state institutions. Elements of social protection of people with the formed military competence include adaptation to civil life, which involves training, retraining, and advanced training in civilian specialties. For the state, this option is not effective in the face of rising unemployment. In the described conditions, it is important to determine the mechanisms of state management of human resources with the established military competencies.